Unravelling androgens in sport: Altrenogest shows strong activation of the androgen receptor in a mammalian cell bioassay. Issue 3 (26th October 2020) - Gillon, Ashley; Ho, Emmie N.M.; Chan, George H.M.; Kauff, Alexia; Hughes, Gillian; Lund, Rachel A.; Ashley, Zoe; Wan, Terence S.M.; Heather, Alison K.
Abstract: Altrenogest is a commonly used progestogen for the suppression of oestrus and associated distracting behaviours that interfere with training and performance of female racehorses. The steroid is derived from 19‐nor testosterone and is structurally similar to the anabolic androgenic steroid, trenbolone. In this study, the relative androgen potency of altrenogest was determined by a kidney (HEK293) cell androgen bioassay. The HEK293 bioassay shows that in its pure form, altrenogest has a high relative potency compared with testosterone but is not as strong as β‐trenbolone. Our results also show that altrenogest is able to activate the androgen receptor at the concentrations relevant to the administration regime of racehorses and retains its activity ex vivo. Thus, we show unequivocally that altrenogest, a progestogen used widely in female racehorses, acts as a strong androgen in a mammalian cell bioassay. Abstract : Altrenogest, a progestogen used for suppression of oestrus in mares, is similar in structure to trenbolone. In this study, we use a mammalian cell bioassay to show that in its pure form, altrenogest is a potent activator of the androgen receptor (AR), stronger than testosterone. Further to this, at concentrations in keeping with the administration regime and in biological matrices, altrenogest was active against AR.